Switchable and tunable metamaterial absorber in THz frequencies - Dang, Hong Luu (ĐHQGHN, 2017)
We demonstrated a metamaterial absorber (MMA), which can be controlled by variation of conductivity or temperature. The metamaterial (MM) structure is based on three individual layers of periodic split ring resonator (SRR), a dielectric, and metallic film. The resonant frequency of the designed structure is numerically investigated at THz range of electromagnetic (EM) wave, which is explained by surface current and equivalent LC-circuit. It was found that by replacing the metallicfilm with VO2, the ab-sorption intensity can be controlled by modification of the conductivity through the optical pumping power, while the absorption frequency is tuned by changing the temperature of InSb materialfilled into two slits of SRR. It is expected that this work will allow switchable and tunable absorption behaviours for applications of MMA